2012
DOI: 10.1038/oby.2012.92
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Profile in Asian Patients Undergoing Coronary Revascularization and Its Association With Plaque Vulnerability: IDEAS‐ADIPO Study

Abstract: Despite potent insulin-sensitizing, anti-inflammatory, and antiatherogenic effects in animal studies, the relationship between serum adiponectin level and coronary artery disease in patients remains unclear. We determined the adiponectin profile in a cohort of multiethnic Asian patients with coronary artery disease, and the association between serum adiponectin level and culprit lesion necrotic core (NC) content. Ninety-four Asian patients (BMI, 25.3 ± 3.7 kg/m 2 ) undergoing percutaneous coronary intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
6
1
Order By: Relevance
“…Given that a high necrotic core plaque content signifies vulnerability and is predictive of subsequent cardiovascular events, our findings were in line with the hypothesis that serum adiponectin level is elevated in a counter-regulatory fashion in advanced coronary artery disease. Yet, in the same study, we found that serum adiponectin levels differed between the three ethnic groups in Singapore [6]. It was significantly lower in the Indian patients than in the Chinese and Malay patients.…”
contrasting
confidence: 46%
See 4 more Smart Citations
“…Given that a high necrotic core plaque content signifies vulnerability and is predictive of subsequent cardiovascular events, our findings were in line with the hypothesis that serum adiponectin level is elevated in a counter-regulatory fashion in advanced coronary artery disease. Yet, in the same study, we found that serum adiponectin levels differed between the three ethnic groups in Singapore [6]. It was significantly lower in the Indian patients than in the Chinese and Malay patients.…”
contrasting
confidence: 46%
“…In the IDEAS (Intravascular Ultrasound Diagnostic Evaluation of Atherosclerosis in Singapore)-ADIPO study, which included a cohort of multi-ethnic Asian populations undergoing coronary revascularization, we reported a positive correlation between serum adiponectin level and necrotic core coronary plaque content [6]. Given that a high necrotic core plaque content signifies vulnerability and is predictive of subsequent cardiovascular events, our findings were in line with the hypothesis that serum adiponectin level is elevated in a counter-regulatory fashion in advanced coronary artery disease.…”
mentioning
confidence: 85%
See 3 more Smart Citations